Drug Extravasation in Pediatric Oncology: Single Center Experience - Betül Sevinir (Güncel Pediatri)
Aim: The frequency of cytotoxic chemotherapy extravasation is uncertain. The aim of this study was to determine extravasation frequency and to verify the risk factors in our center.Materials and Methods: Hospital records of pediatric oncology patients at Uludağ University Faculty of Medicine, Department of Pediatric Oncology between 2004-2007 were reviewed retrospectively. Number of the cases with chemotherapy extravasation, diagnosis, demographic and clinical features were recorded. Results: The incidence of cytotoxic drug extravasation in pediatric oncology cases was 0.4%. Forty-one percent of extravasations were observed in patients under 3 years The median extravasation time was 9th week of the chemotherapy. Most of the extravasation injuries were seen in outpatient clinic (77%) and mainly in cases who were having therapy weekly (59%). The most frequent site of extravasation was dorsal hand (82%). Causative drugs were vinca alkaloids, doxorubicin and dactinomycin.Conclusion: The incidence of chemotherapy induced extravasations were similar with literature. Young age and weekly chemotherapy were major risk factors in pediatric oncology cases. (Journal of Current Pediatrics 2008; 6: 1-4)